Mechanism of Anticipatory Adjustments of the H Reflexes of the Shin Muscles in Humans Related to Voluntary Movements in the Contralateral Ankle Joint - Ivanchenko, Ye. Z.; Slivko, E. I.; Іванченко, Олена Зенонівна; Сливко, Емануіл Ілліч (My University, 2013)
In healthy adults, we recorded H reflexes from the mm. sloeus and tibialis longus; the reflexes were evoked by transcutaneous stimulation of the n. tibialis comm. and n. peroneus comm., respectively. Changes in the magnitude of the H reflexes were measured, and background EMG activity was recorded from the tested muscles within a premotor period of voluntary plantar flexion of the foot of the contralateral lower limb performed by a light signal. The EMG activity appearing in the m. soleus of the latter lower limb served as the index of beginning of the conditioning movement. Anticipatory facilitation of the H reflexes in both tested muscles, which began 60-90 msec before initiation of the conditioning contralateral movement, was observed. The magnitudes of these reflexes increased gradually and reached their maxima synchronously with the greatest EMG level in the contralateral m. soleus. Background EMGs recorded from both tested muscles demonstrated no significant changes within the premotor period. The above-described results show that anticipatory facilitation of the H reflexes of the shin muscles within the mentioned period of the voluntary movement of the contralateral lower limb is related to changes developing in the presynaptic components of the arcs of these reflexes. It is hypothesized that such changes result from weakening of background presynaptic inhibition in the terminals of 1a afferents of the testes muscles under the influence of descending activity coming from the supraspinal structures. Weakening of presynaptic inhibition promotes facilitation of the afferent signals arriving from proprioceptors and providing regulation of changes in the nervous system within the premotor period.